Manifestations of Viral Diseases of the Oral Mucosa, Herpes Simplex and Herpes Zoster, Herpangina, Clinical Features, Comparative Diagnosis and Treatment - Xusan, Jahongirov; Sunnat, Farmonov; Azizbek, Rahmiddinov; Jasurbek, Xasanov; Hikmatullayevna, Marupova Madina (American Journal of Bioscience and Clinical Integrity, 2025)
Shingles, also known as herpes zoster, is a viral infection that occurs when the varicella-zoster virus becomes active and remains dormant in the body after a chickenpox infection. The virus enters the body through the skin and mucous membranes, causing characteristic symptoms such as redness, itching, blisters, and a painful rash. The intercostal or trigeminal nerves are most often affected. The rash is accompanied by severe pain. Herpes spreads through the body, as if following the nerve trunk, which is why it got its name. The incubation period of this disease can last from several days to several weeks, during which the virus actively multiplies in skin cells and nerve endings. Shingles occurs mainly in people over 50 years old, both women and men, because with age the immune system weakens and the body is unable to resist the virus. The development and course of the disease cannot be predicted, its initial symptoms can vary significantly and depend on the form of the disease and its severity.